Thalassaemia in Sri Lanka: implications for the future health burden of Asian populations. Sri Lanka Thalassaemia Study Group. - de Silva, S; Fisher, C; Premawardhena, A; Lamabadusuriya, S; Peto, T; Perera, G; Old, J; Clegg, J; Olivieri, N; Weatherall, D (2000)
BACKGROUND: Thalassaemias pose an increasing problem for the Indian subcontinent and many Asian countries. We analysed the different types of thalassaemia in the Sri Lankan population, surveyed gene frequencies in schoolchildren, and estimated the burden of disease and requirements for its control. METHODS: We analysed blood samples from patients attending clinics in nine hospitals and defined the different types of beta thalassaemia by high-performance liquid chromatography (HPLC) and DNA analysis. The range of mutations was obtained by analysis of beta-globin genes. Capillary blood was obtained from schoolchildren from different parts of the island and analysed by HPLC to provide an approximate assessment of the carrier frequency of beta thalassaemia and haemoglobin E (HbE). To estimate the frequency of alpha thalassaemia the alpha-globin genotypes were also analysed when it was possible. FINDINGS: Blood samples were obtained from 703 patients with beta thalassaemia and from 1600 schoolchildren. The thalassaemia mutations were unevenly spread. Although 23 different beta-thalassaemia mutations were found, three accounted for the thalassaemia phenotype in about 70% of the patients, most whom are homozygotes or compound heterozygotes for IVS1-5 (G-->C) or IVS1-1 (G-->A). The third common mutation, codon 26 (G-->A), which produces HbE, interacts with one or other of these mutations to produce HbE/beta thalassaemia; this comprises 13.0-30.9% of cases in the main centres. Samples from 472 patients were analysed to determine the alpha-globin genotype. Overall, 15.5% patients were carriers for deletion forms of alpha+ thalassaemia. Average gene frequencies showed that there will be more than 2000 patients requiring treatment at any one time, in the future, of whom those with HbE/beta thalassaemia will account for about 40%. INTERPRETATION: In Sri Lanka, interactions of the two common beta-thalassaemia alleles will nearly always result in a transfusion-dependent disorder. However, about 40% of patients will have HbE/beta thalassaemia, which has a variable course. The management of these disorders could require about 5% of the total health budget. We need to learn more about the natural history and appropriate management of HbE/beta thalassaemia if resources are to be used effectively.